A multi-fidelity approach for aerodynamic performance computations of formation flight - Singh, Diwakar; Antoniadis, Antonis F.; Tsoutsanis, Panagiotis; Shin, Hyo-Sang; Tsourdos, Antonios; Mathekga, Samuel; Jenkins, Karl W. (MDPI, 2018)
This paper introduces a multi-fidelity computational framework for the analysis of aerodynamic performance of flight formation. The Vortex Lattice and Reynolds Averaged Navier–Stokes methods form the basis of the framework, as low- and high-fidelity, respectively. Initially, the computational framework is validated for an isolated wing, and then two rectangular NACA23012 wings are considered for assessing the aerodynamic performance of this formation; the optimal relative position is through the multi-fidelity framework based on the total drag reduction. The performance estimates are in good agreement with experimental measurements of the same configuration. Total aerodynamic performance of formation flight is also assessed with respect to attitude variations of the lifting bodies involved. The framework is also employed to determine the optimal position of blended-wing-body unmanned aerial vehicles in tandem formation flight.
Keywords: multi-fidelity; aerodynamic performance; formation; VLM; RANS